Harvey Cushing, father of contemporary neurosurgery - Ricardo Hodelín Tablada; Ricardo Hodelín Fuentes (Centro Provincial de Información de Ciencias Médicas, 2019)
Neurosurgery as specialty began in the second half of the XIX century and its name is due to the initiative of the doctor Harvey Cushing who, after carrying out a journey for European lands, returned to the United States and was entirely devoted to the nervous system surgery. Some aspects related to his childhood and adulthood are pointed out in this work, as well as his admission to Johns Hopkins Hospital, his participation in the First World War and his consolidation as neurosurgeon from 1912 to 1932; when he worked at Peter Bent Brigham Hospital. His contributions to this branch of medicine and to other branches, his surprising scientific production, integrated by 24 books and 658 articles, and his different rewards, such as the Pulitzer Prize in 1926 are also remarkable. Finally, his fundational role of the Society Neurological Surgeons is recognized, that adopted the name Harvey Cushing Society and today is the American Association of Neurological Surgeons. The aim of these pages is to pay tribute to this distinguished physician, father of the contemporary neurosurgery.